Neuro-emotions based on electroencephalograph response to different color Ardisia mamillata Hance plants in elderly people with and without cognitive impairment - Juan Du; Xiaomei Chen; Xi Li; Yuanzhi Pan; Erkang Fu; Yumei Huang; Chunyan Zhu; Mingyan Jiang; Ahmad Hassan; Dingru Wu; Jun Ma; Guangsheng Yuan (Frontiers Media S.A., 2022)
BackgroundGiven the aging population, the quality of mental health of elderly people deserves special attention. The aims of this study were (1) to assess the difference of neuro-emotion based on EEG from the cognitively impaired elderly (CNE) and the cognitively normal elderly (CIE) participants viewing different color Ardisia mamillata Hance and (2) to determine which color Ardisia mamillata Hance has greater benefits for boosting their neuro-emotions.MethodsThe cognitive function of the participants was judged by using the revised Chinese version of the Mini-Mental State Examination (MMSE) scale combined with the daily cognitive performance of the participants, and the participants were divided into the cognitive normal elderly (CNE) and the cognitive impairment elderly (CIE). A total of 10 CNE volunteers and 10 CIE volunteers were recruited as participants for this study. For this study, two varieties of Ardisia mamillata Hance, green tiger tongue (GTT) with green leaves and red tiger tongue (RTT) with reddish brown leaves, were observed as plant materials. In total, six emotional indexes, including stress, engagement, interest, excitement, focus, and relaxation, were then measured by electroencephalography (EEG).ResultsRTT had the most positive effect on EEG neuro-emotion in the CNE group, with significant reductions in stress, engagement, and focus in the RTT test, while the combination of GTT+RTT had a positive effect on EEG neuro-emotions in the CIE group, with significant reductions in engagement and focus in the GTT+RTT test. No statistically significant differences were found for the interest, excitement, and relaxation index in the CNE and CIE participants in all tests.ConclusionSignificant reductions were observed in stress, engagement, and focus values of the CIE participants in the RTT test, which indicated that the CNE participants were more relaxed. RTT is a reddish brown and warm color plant, so the CNE individuals should always have the warm color plants indoors or outdoors, which could help boost their neuro-emotions. Significant reductions were observed in engagement and focus values of the CIE participants in the GTT+RTT test, which indicated that the CIE participants were more relaxed. The combination of GTT+RTT test shows the combination cold and warm color plants; therefore, the CIE individuals should always have a combination of cool and warm color plants indoors or outdoors, which could help boost their EEG neuro-emotions.